Understanding Hospitals in Changing Health Systems
XXV, 242 p. 8 illus.
Keywords: “This timely book provides insight into the changing role of the ‘hospital’ in the face of technological, organizational innovation and ever-tightening health budgets.” James Barlow, Imperial College Business School, UK “The book covers aspects of hospitals in different states and contexts. Underlining the importance of business models, it presents models of care from historic and current perspectives. All authors possess deep insight into health care systems, as scholars and experts working for world-renowned health policy institutions like the World Health Organization, World Bank or European Observatory.” Siegfried Walch, Management Center Innsbruck, Austria “For an organisation like mine, representing those involved in the strategic planning of healthcare infrastructure, this book provides invaluable insights into what really matters – now and for the future – in the complex and contentious field of hospitaldevelopment.” Jonathan Erskine, European Health Property Network, Netherlands This book seeks to reframe current policy discussions on hospitals. Healthcare services turn expensive economic resources - people, capital, energy, materials - into care. Hospitals concentrate the use and cost of this. But paradoxically other areas of health, such as public health and primary care, attract more attention and affection, at least within the health policy community. Hospitals choose, or are assigned, to deliver certain parts of care packages. They are organised to do this via business models. These necessarily incorporate care models – the processes that patients follow. The activity needs to be governed, in the widest senses. Rational decisions need to be taken about care and resources used. This book pulls these elements together, to stimulate a debate. Antonio Durán is Alldmh Consultancy director, senior consultant for WHO, WB, EU and DfID, and Technical Adviser for the European Observatory on Health Systems. A frequent lecturer and speaker, he has recently published peer-reviewed articles, and edited a book on governing public hospitals. Stephen Wright is a freelance consultant in health policies, macroeconomics, social investment, and health finance and investment, for EU Member States, European Commission, EIB, WB and WHO. He has co-edited a number of books, and publishes and presents frequently.